Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1212/wnl.0000000000200932
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Function and Sleep Disordered Breathing in Pediatric Duchenne Muscular Dystrophy

Abstract: Background:The decline of respiratory function in Duchenne muscular dystrophy (DMD) is associated with sleep disordered breathing (SDB) and alteration of nocturnal gas exchange, first manifesting as nocturnal hypoventilation (NH). However, the correlation between pulmonary function measured by spirometry (PFT) and the onset of SDB with or without NH is unclear.Aim:To identify the prevalence and features of SDB and to investigate the relationship between lung function determined by forced vital capacity (FVC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…Patients with CMD had the highest prevalence of hypoventilation, but it was also common in patients with DMD and DM; patients with LGMD had the lowest prevalence though differences in hypoventilation prevalence among types were not statistically significant. In a recent study of patients with DMD in their early teens,34 ~34% had hypoventilation; this proportion is somewhat lower than in our patients with DMD. Hypoventilation in patients with muscular dystrophy is usually most severe in rapid eye movement sleep 18…”
Section: Discussioncontrasting
confidence: 73%
“…Patients with CMD had the highest prevalence of hypoventilation, but it was also common in patients with DMD and DM; patients with LGMD had the lowest prevalence though differences in hypoventilation prevalence among types were not statistically significant. In a recent study of patients with DMD in their early teens,34 ~34% had hypoventilation; this proportion is somewhat lower than in our patients with DMD. Hypoventilation in patients with muscular dystrophy is usually most severe in rapid eye movement sleep 18…”
Section: Discussioncontrasting
confidence: 73%
“…They advocated for the necessity of early screening, particularly within the first 3 years after the loss of ambulation (LOA), even in individuals with FVC > 50%. 42 There has been increasing interest in SDB in children with spinal muscular atrophy (SMA) due to the high prevalence of respiratory complications in this population. With the development of disease-modifying therapies like nusinersen and onasemnogene-abeparvovec, there has been a shift in the management of SMA type 1 from palliative to proactive.…”
Section: Sleep In Neuromuscular Disordersmentioning
confidence: 99%
“…It is worth mentioning that in this cohort only 38% were patients with DMD. The retrospective study by Zambon et al 42 evaluated 134 patients with DMD and found that borderline NHH was detected in 31 patients. Only nonambulant patients in this cohort had frank NHH ( N = 14).…”
Section: Sleep In Neuromuscular Disordersmentioning
confidence: 99%
“…These include children with Trisomy 21, craniofacial anomalies, craniosynostoses, achondroplasia, and with neuromuscular disorders (ElMallah et al, 2017). Though AT is still considered the first line of treatment, these children have higher rates of residual OSA (Rosen, 2011;Zandieh et al, 2013;Cielo and Marcus, 2015;Moraleda-Cibrián et al, 2015;Thottam et al, 2015;Simpson et al, 2018;Zambon et al, 2022), often requiring additional therapy. Positive pressure may be added to treat residual disease or primarily used in those unsuitable for AT (Muntz, 2012;Nehme et al, 2019).…”
Section: Introductionmentioning
confidence: 99%